PENCEGAHAN KEJAHATAN PEOPLE SMUGGLING OLEH DIREKTORAT KEPOLISIAN PERAIRAN POLDA RIAU - Petrus Lamhot; Firdaus '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
People smuggling occurred in Riau Province , this is because there are some areas in Riau waters immediately adjacent to some neighboring countries such as Malaysia, Singapore, thus becoming crossings for human smuggling. Type of this research is classified as socio-juridical research , because in this study the authors directly conduct research on the location or place under study in order to provide a complete and clear picture of the problem under study. The research problems are , among others : the first, Are the causes of the crime of people smuggling between the State , the second , and the implementation of preventive mechanisms What people smuggling by Riau Police Directorate of Water Police and Immigration Pekanbaru , third , How the efforts made Riau Police Directorate of Water Police and Immigration Pekanbaru to overcome the obstacles encountered in doing crime prevention against people smuggling. The results of the study are: first , the People smuggling sesungguhya departing from the urge to be illegal immigrants , second , mechanism and implementation of prevention Direktotorat people smuggling by Riau Police Water Police and Immigration Pekanbaru with pre entif efforts among others ; FLOAT training , do counseling or socialization , improve village sambang activities , conducting public information waters , the establishment of information networks , patrol dialogue , and the survey of the ship owner , third , efforts to overcome barriers to people smuggling crime prevention is to improve the internal factors and factors external such an act is to provide guidance , supervision , improve facilities and infrastructure in performing police duties , increase public knowledge of the immigration laws , increased surveillance against illegal port.